PENGARUH PENAMBAHAN KONSENTRASI SUSU SAPI DAN WAKTU FERMENTASI TERHADAP KUALITA`S SOYGHURT - Jayanti, Septi; Bintari, Siti Harnina; Iswari, Retno Sri (Life Science, 2015)
Pembuatan tempe yang memerlukan banyak air menyebabkan banyaknya limbah cair yang dihasilkan, salah satunya yaitu rebusan kedua kedelai. Limbah cair tersebut masih mengandung banyak senyawa-senyawa organik seperti protein, karbohidrat, lemak, dan minyak., sehingga masih dapat dimanfaatkan sebagai bahan dasar minuman seperti yoghurt kedelai atau soyghurt. Penelitian ini bertujuan untuk mengetahui bagaimana pengaruh konsentrasi susu dan waktu fermentasi terhadap kadar total asam laktat, jumlah bakteri asam laktat soyghut, dan tingkat kesukaan masyarakat. Konsentrasi susu sapi yang digunakan yaitu 10%, 20%, dan 30%. Sedangkan waktu fermentasinya yaitu 4, 6, 8, dan 10 jam. Metode yang dilakukan dalam penelitian ini adalah penelitian eksperimental dengan 12 perlakuan dan 3 kali ulangan.Hasil penelitian menunjukkan bahwa kadar asam laktat tertinggi terdapat pada soyghurt dengan penambahan susu sapi sebanyak 30% dengan waktu fermentasi 10 jam. Jumlah bakteri asam laktat (BAL) dari tiap perlakuan tidak terdapat perbedaan yang signifikan. Hasil uji organoleptik didapatkan soyghurt dengan penambahan susu sapi 30% dengan waktu fermentasi 10 jam paling disukai oleh panelis.Dari hasil penelitian tersebut dapat disimpulkan bahwa penambahan konsentrasi susu sapi dan waktu fermentasi berpengaruh terhadap kadar asam laktat dan tingkat kesukaan masyarakat tetapi tidak berpengaruh terhadap jumlah bakteri asam laktat Making tempe that require a lot of water caused many wastewater produced, one of which is both soybean stew. The liquid waste still contains a lot of organic compounds such as proteins, carbohydrates, fats, and oils., So that they can be used as a basic ingredient of beverages such as soy yogurt or soyghurt. This study aims to determine how the effect of milk concentration and time of fermentation on total levels of lactic acid, the amount of lactic acid bacteria soyghut, and the level of community preferences. Concentration of cow's milk used are 10%, 20%, and 30%. While the fermentation time is 4, 6, 8, and 10 hours. The method used in this research is experimental research with 12 treatments and 3 repetitions. The results showed that the highest levels of lactic acid found in cow's milk soyghurt with the addition of as much as 30% with a fermentation time of 10 hours. Moderate to BAL number of every treatment there is no significant difference. From the results obtained soyghurt organoleptic test by the addition of 30% cow's milk fermentation time of 10 hours panelis. From most favored by these results we can conclude that the addition of cow's milk concentration and fermentation time effect on lactic acid levels and A levels of society but does not affect the amount of lactic acid bacteria Making tempe that require a lot of water caused many wastewater produced, one of which is both soybean stew. The liquid waste still contains a lot of organic compounds such as proteins, carbohydrates, fats, and oils., So that they can be used as a basic ingredient of beverages such as soy yogurt or soyghurt. This study aims to determine how the effect of milk concentration and time of fermentation on total levels of lactic acid, the amount of lactic acid bacteria soyghut, and the level of community preferences. Concentration of cow's milk used are 10%, 20%, and 30%. While the fermentation time is 4, 6, 8, and 10 hours. The method used in this research is experimental research with 12 treatments and 3 repetitions. The results showed that the highest levels of lactic acid found in cow's milk soyghurt with the addition of as much as 30% with a fermentation time of 10 hours. Moderate to BAL number of every treatment there is no significant difference. From the results obtained soyghurt organoleptic test by the addition of 30% cow's milk fermentation time of 10 hours panelis. From most favored by these results we can conclude that the addition of cow's milk concentration and fermentation time effect on lactic acid levels and A levels of society but does not affect the amount of lactic acid bacteria